Aggregate savings and external imbalances in China - Dennis Tao Yang (Institute for the Study of Labor (IZA), 2012)
Over the last decade, the internal and external macroeconomic imbalances in China have risen to unprecedented levels. In 2008, China's national savings rate soared to over 53 percent of its GDP, whereas its current account surplus exceeded 9 percent of GDP. The current paper presents a unified framework for understanding the structural causes of these imbalances. I argue that the imbalances are attributable to a set of policies and institutions embedded in the economy. Moreover, the accession of China to the World Trade Organization has dramatically amplified the effects of these structural distortions. I document major trends in aggregate savings, investment, trade, and net foreign asset positions in China, and explore options for policy reforms aimed at rebalancing the Chinese economy.
Keywords: E21; O16; F32; 330; aggregate savings; current account; income distribution; structural distortions; trade policies; China; Sparen; Leistungsbilanz; Zahlungsbilanzungleichgewicht; Einkommensverteilung; Außenwirtschaftspolitik; China